Isolation of Coumarins, Polymethoxylated Flavonoids, and Triterpenoids from Citrus grandis (Tubtim Siam Cultivar) Leaves and Evaluation of Their Biological Activities - Uraiwan Phetkul; Thitikorn Prombanchong; Saowanee Maungchanburi; Supakit Paosen; Kewalee Chaichan (Natural Resources for Human Health, 2026)
Citrus grandis cv. Tubtim Siam is an economically important pomelo cultivar in Thailand. Although the phytochemical constituents of its fruit tissues have received attention, information regarding the chemical composition and biological properties of its leaves remains limited. As leaves represent a potential source of bioactive secondary metabolites, the present study aimed to isolate and identify the major constituents of C. grandis leaves and evaluate their biological activities. Phytochemical investigation of the leaves resulted in the isolation of six compounds: two coumarins, 7,8-dimethoxycoumarin (2) and 6,7-dimethoxycoumarin (3); two polymethoxylated flavonoids, tangeretin (4) and nobiletin (5); and two triterpenoids, friedelin (1) and limonin (6). Their structures were elucidated by NMR spectroscopic analysis and comparison with published data. The extract and selected compounds were evaluated for antioxidant, antibacterial, and antiproliferative activities. Among the tested samples, tangeretin exhibited the strongest antioxidant activity (IC50 = 1.86 ± 0.42 µg/mL), while the crude extract also demonstrated notable radical-scavenging activity (2.30 ± 0.08 µg/mL), suggesting that multiple constituents may collectively contribute to the observed antioxidant activity. In contrast, all samples demonstrated weak antibacterial and antiproliferative activities under the experimental conditions. The results indicate that the biological relevance of C. grandis leaves is primarily associated with antioxidant properties rather than antibacterial or antiproliferative effects. The phytochemical profile suggests tissue-specific distribution of secondary metabolites in citrus species and provides chemotaxonomic insights into this cultivar. This study expands current knowledge of the phytochemical constituents of C. grandis leaves and supports their potential as a natural source of antioxidant agents.